MEMORABLE TOURIST EXPERIENCE AND REVISIT INTENTION: THE MEDIATING ROLE OF DESTINATION IMAGE - Mohammad Faidlur Rahman; Mar’atul Fahimah (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
Sustainable tourism is a key focus in the development of tourist destinations in Indonesia, including Ketapanrame Village, Trawas, one of the nation's best tourist villages. Although the number of tourist visits tends to increase, fluctuations in visits indicate the need for strategies to encourage sustainable revisit intentions. This study aims to analyze the influence of Memorable Tourist Experience (MTE) on revisit intentions, with destination image as a mediating variable. The study used a quantitative approach through questionnaires conducted with tourists who had visited Sumber Gempong and Ghanjaran Park in the past two years. Data analysis was conducted using Structural Equation Modeling (SEM). The results show that MTE has a positive and significant effect on destination image and revisit intentions, while destination image also has a positive effect on revisit intentions and mediates the effect of MTE. These findings emphasize the importance of memorable tourist experiences in building destination image and increasing tourist loyalty, thus supporting the sustainability of tourism in Ketapanrame Village.